Cultural adaptation and validation of the Freiburg Life Quality Assessment - Wound Module to Brazilian Portuguese - Elaine Aparecida Rocha Domingues; Neusa Maria Costa Alexandre; José Vitor da Silva (Universidade de São Paulo, 2016)
Objectives: to adapt the Freiburg Life Quality Assessment - Wound Module to Brazilian Portuguese and to measure its psychometric properties: reliability and validity. Method: the cultural adaptation was undertaken following the stages of translation, synthesis of the translations, back translation, committee of specialists, pre-test and focus group. A total of 200 patients participated in the study. These were recruited in Primary Care Centers, Family Health Strategy Centers, in a philanthropic hospital and in a teaching hospital. Reliability was assessed through internal consistency and stability. Validity was ascertained through the correlation of the instrument's values with those of the domains of the Ferrans and Powers Quality of Life Index - Wound Version and with the quality of life score of the visual analog scale. Results: the instrument presented adequate internal consistency (Cronbach alpha =0.86) and high stability in the test and retest (0.93). The validity presented correlations of moderate and significant magnitude (-0.24 to -0.48, p<0.0001). Conclusion: the results indicated that the adapted version presented reliable and valid psychometric measurements for the population with chronic wounds in the Brazilian culture.